Long-Term Use of a Sensory Prosthesis Improves Function in a Patient With Peripheral Neuropathy: A Case Report - Wrisley, Diane M.; McLean, Gillian; Hill, Jennifer Baity; Oddsson, Lars I. E. (Frontiers in Neurology, 2021)
Background: Peripheral neuropathy (PN) can result in either partial or complete loss of distal sensation resulting in an increased fall risk. Walkasins® uses a shoe insert to detect the magnitude and direction of sway and sends signals to a leg unit that provides sensory balance cues. The objective of this case report is to describe the long-term influence of the Walkasins® lower limb sensory neuroprosthesis on balance and gait for an individual with diabetic PN. Case Description: A fifty-one-year-old male with a 3-year history of PN and a 10-year history of type II diabetes mellitus was fitted with Walkasins® and utilized the shoe inserts 8-10 hours/day for more than 1 year. Although, vibration and tactile thresholds were severely impaired at his 1st metatarsophalangeal joint and the lateral malleolus bilaterally he could perceive tactile stimuli from the Walkasins® above the ankles. Outcomes: Following Walkasins® use, his Activities-specific Balance Confidence Scale (ABC) scores improved from 33% to 80%. His mean Vestibular Activities of Daily Living (VADL) scores decreased from 3.54 to 1. His Functional Gait Assessment (FGA) scores increased from 13/30 to 28/30 and his miniBESTest scores improved from 15/28 to 26/28. Gait speed increased from 0.23 m/sec to 1.5 m/sec. The patient described a decrease in pain and cramping throughout his lower extremities and an increase in function. Discussion: Gait and balance improved with the use of the Walkasins® and participation in the Neuro Wellness Program. This improvement suggests that the use of sensory substitution devices, such as the Walkasins®, may replace sensory deficits related to gait and balance dysfunction experienced by patients with PN. Further research is needed to determine if other patients will have a similar response and what the necessary threshold of sensory function is to benefit from use of the Walkasins®.